Digital Finance and Social Media: A Bibliometric Analysis of Financial Influencers - Renuka, T.; Swaminathan, Usha (International Review of Management and Marketing, 2025)
This study investigates the progressive research landscape concerning financial influencers (“finfluencers”), the impact of social media on investor sentiment, and the incorporation of artificial intelligence (AI) in financial decision-making processes. By employing data derived from the Scopus database, this examination assesses research productivity, citation impact, and thematic trends across 182 scholarly publications spanning from 2012 to 2025. The principal findings reveal an increasing focus on digital financial literacy, behavioural finance, and computational finance, with AI-driven sentiment analysis assuming a pivotal role in stock market forecasting and investment methodologies. The investigation underscores the globalized nature of academic collaborations, highlighting substantial contributions from China, the United Kingdom, India, and the United States. Furthermore, the findings underscore the escalating regulatory scrutiny surrounding financial influencers and the ethical ramifications associated with algorithmic finance. This study recognizes limitations such as dependence on Scopus-indexed documents and the potential for publication biases. Moreover, there is a pressing need for further investigation into the regulatory frameworks governing finfluencers to ensure the provision of responsible financial guidance across digital platforms. It highlights the significance of interdisciplinary research in comprehending the nexus of financial markets, AI, and social media dynamics, thereby laying the groundwork for forthcoming scholarly and policy-oriented dialogues.